The Effect of Financial Compensation, Performance Assessment, and Competencies on the Performance of High School Teachers - Khairiah Khairiah; Zuraida Zuraida; Heru Fahlevi (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to examine the effect of financial compensation, performance appraisal, and competence on the performance of senior high school teachers in Banda Aceh City. The research was conducted in a senior high school in Banda Aceh City. The population of this study was 30 high school seniors consisting of 19 senior high schools, 6 vocational high schools, 3 state madrasah aliyah, and 2 integrated dayah. This study uses a mixed method. The research data was obtained by distributing questionnaires and interviews. The data is then analyzed quantitatively and qualitatively. The results of the study showed that 1) The results of quantitative calculations, financial compensation and teacher competence jointly affect teacher performance, but performance appraisal does not affect the performance of senior high school teachers in Banda Aceh City. Partially, there is an effect of financial compensation and teacher competence on the performance of high school teachers in Banda Aceh City. However, there is no effect of performance appraisal on the performance of senior high school teachers in Banda Aceh City. 2) Qualitatively, the results of interviews with principals showed financial compensation and teacher competence. Meanwhile, teacher performance appraisal only affects teacher performance if there is feedback and supervision from the principal. According to school principals, other factors that influence teacher performance are internal and external factors, namely the motivation and character of teachers, which are supported by the leadership and work environment.